Understanding relativity : a simplified approach to Einstein's theories - Sartori, Leo. (Berkeley : University of California Press, 1996)
This extraordinary guide makes Einstein's theory of relativity accessible to readers with a minimum knowledge of physics and algebra. Through effective diagrams and an emphasis on the logical structure of the theory, Leo Sartori clearly presents the relativistic concepts of time, space, and energy and makes understandable the aspects of the theory that seem counterintuitive. Understanding Relativity includes an introduction to general relativity and cosmology, but focuses on special relativity. Sartori traces the historical development of the theory and carefully explains its implications. He explores illuminating paradoxes, including the famous twin paradox and the "pole-in-the-barn" paradox, and describes the Loedel diagram, which is an accessible, graphical approach to relativity. Students of the history and philosophy of science will welcome this concise introduction to one of the cornerstones of modern physics
ch. 1. Galilean relativity -- ch. 2. Michelson-Morley experiment -- ch. 3. Postulates of relativity and their implications -- ch. 4. Lorentz transformation -- ch. 5. Space-time diagrams -- ch. 6. Paradoxes of relativity -- ch. 7. Relativistic mechanics -- ch. 8. General relativity -- ch. 9. Cosmology.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Relativity (Physics); Relativité (Physique); SCIENCE -- Physics -- Relativity; SCIENCE -- General; Relativity (Physics); Relativity